Un paseo de compras problematico - Jules, Jacqueline, 1956-; Smith, Kim, 1986- (North Mankato, Minnesota : Picture Window Books, a Capstone imprint, 2018)
The whole Martinez family is shopping for back-to-school supplies, and Sofia is excited by the colorful backpacks and fancy notebooks--but excitement turns to alarm when four-year-old Manuel disappears.
Accelerated Reader AR
In Spanish.
Keywords: Missing children -- Juvenile fiction; Hispanic American children -- Juvenile fiction; Hispanic American families -- Juvenile fiction; Shopping -- Juvenile fiction; Spanish language materials; Familias hispanoestadounidenses -- Novela juvenil; Ninos hispanoestadounidenses -- Novela juvenil; Compras personales -- Novela juvenil; Ninos desaparecidos -- Novela juvenil